2014
DOI: 10.5558/tfc2014-013
|View full text |Cite
|
Sign up to set email alerts
|

Potential opportunities to utilize mountain pine beetle-killed biomass as wood pellet feedstock in British Columbia

Abstract: The use of renewable forms of energy, such as bioenergy produced from wood pellets, can serve to offset fossil fuel use and, hence, reduce greenhouse gas emissions. The European Union is the world's largest user of wood pellets and British Columbia has been one of its largest external suppliers. British Columbia is currently grappling with the largest mountain pine beetle outbreak in its history. While this outbreak is expected to decrease the future timber supply in the Province, it has been suggested that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The future availability of residues is, however, in jeopardy as BC enters the mid-term supply gap (MFLNRO 2012). With current pellet production capacity being accustomed to harvests in the annual allowable cut uplifts, pellet companies may well be faced with less economic whole-tree harvesting and chipping of harvest residues in the future (Lloyd et al 2014). Our study looked at whole-tree harvesting of these stands (scenario 2) and found that pellets can contribute significant C emissions if forest management in BC is not meeting C-neutral forestry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The future availability of residues is, however, in jeopardy as BC enters the mid-term supply gap (MFLNRO 2012). With current pellet production capacity being accustomed to harvests in the annual allowable cut uplifts, pellet companies may well be faced with less economic whole-tree harvesting and chipping of harvest residues in the future (Lloyd et al 2014). Our study looked at whole-tree harvesting of these stands (scenario 2) and found that pellets can contribute significant C emissions if forest management in BC is not meeting C-neutral forestry.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of timber in these two cases greatly affects the release of C following the harvest of MPB stands. While pre-outbreak stands were traditionally harvested for lumber, the expected degradation in MPB wood quality has many looking to expand its use as a feedstock for softwood pellet production (Lloyd et al 2014). Pellets provide a renewable source of energy and a reduction in fossil fuel consumption and GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Canada's forest sector was affected by the drastic changes in demand for forest products over the course of the pandemic, a trend also observed in the United States [6]. Although the Canadian forest sector is well acquainted with market shocks and had taken steps to mitigate anticipated risks [7,8], it was unclear how exactly the sector would be affected at the onset of the COVID-19 pandemic and how these impacts would spill over Energies 2022, 15, 3179 2 of 18 into related industries. Early analysis of forest-related industries suggests varied experience; despite initial slowdowns, the lumber industry experienced a boom as consumers invested in home improvement projects, while the decline in the pulp and paper industry accelerated as demand for office printing supplies decreased [3].…”
Section: Introductionmentioning
confidence: 99%
“…This scenario reflects growing scientific curiosity (Lamers et al 2014, Lloyd et al 2014), claims by government and industry (EMPR 2007(EMPR , 2008; BC Hydro 2012), concerns of non-governmental organizations (Nikiforuk 2011, Greenpeace 2011, RSPB 2012, and in some cases, actual practice.…”
Section: Experimental Unit and Treatmentmentioning
confidence: 99%
“…The designation of SFM is thought to be legitimatized through its SFM certification process. This negates the fact, however, that SFM certification programs have failed to incorporate global C cycles and climate change as part of their criteria and indicators for SFM designation (Tittler et al 2001, Lloyd et al 2014.…”
Section: Indirect Influences Of the Biological System On Forest Produmentioning
confidence: 99%